PEMIKIRAN TEORI KOGNITIF PIAGET DI SEKOLAH DASAR - Helda Kusuma Wardani (Khazanah Pendidikan, 2022)
Jean Piaget is a psychologist who contributed greatly to the world of education, there are at least two contributions piaget, namely the theory of cognitive learning and the theory of human cognitive development.  Piaget's theory explains that human knowledge is essentially considered active, namely: knowing means acting on objects and realities, and building a system of transformations that can be done on or with them. Piaget stresses that the cognitive processes children use as they build their knowledge of the world are essential: schema, assimilation and accommodation, organization, and equilibrium. Piaget divides the cognitive development of children and adolescents into four stages: sensory-motor, preoperative, concrete operations, and formal operations. Elementary school students are at the stage of concrete operational thinking. Student learning activities are given concrete experiences. Through concrete experience students will easily find concepts. One of them can be done by playing. Piaget believes that playing will foster intrinsic motivation from students. This theory focuses on the active role of children in learning activities. A child not only receives material instantly but the child is guided and directed to discover the concept of material.